Assessment of Elemental Composition in Multivitamin Preparations Marketed in Libya: Implications for Safety and Efficacy - Jamal Elbakay; Amal Belaid; Aya Ben Barka; Hawa Danouni (AlQalam Journal of Medical and Applied Sciences, 2024)
This study evaluates the actual and labeled amounts of macro and trace elements in five multivitamin preparations marketed in Libya, utilizing inductively coupled plasma optical emission spectrometry (ICP-OES). The analysis focuses on essential minerals such as calcium (Ca), copper (Cu), iron (Fe), magnesium (Mg), manganese (Mn), selenium (Se), and zinc (Zn), alongside common heavy metals including arsenic (As), cadmium (Cd), and lead (Pb). The findings reveal significant discrepancies between the actual and labeled amounts of certain elements, raising concerns regarding the safety and efficacy of these supplements for long-term consumption. تُقيّم هذه الدراسة الكميات الفعلية والمُعلنة للعناصر الكلية والنادرة في خمسة مستحضرات متعددة الفيتامينات تُسوّق في ليبيا، باستخدام تقنية التحليل الطيفي للانبعاثات الضوئية بالبلازما المقترنة حثيًا (ICP-OES). تُركز التحليلات على المعادن الأساسية مثل الكالسيوم (Ca)، النحاس (Cu)، الحديد (Fe)، المغنيسيوم (Mg)، المنغنيز (Mn)، السيلينيوم (Se)، والزنك (Zn)، بالإضافة إلى المعادن الثقيلة الشائعة مثل الزرنيخ (As)، الكادميوم (Cd)، والرصاص (Pb). وقد كشفت النتائج عن وجود تباينات كبيرة بين الكميات الفعلية والمُعلنة لبعض العناصر، مما يثير مخاوف بشأن سلامة وكفاءة هذه المكملات عند استخدامها على المدى الطويل